2014
DOI: 10.1590/s1679-45082014rc3110
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative stress and plasma lipoproteins in cancer patients

Abstract: Objective To evaluate the relation between oxidative stress and lipid profile in patients with different types of cancer.Methods This was an observational cross-sectional. A total of 58 subjects were evaluated, 33 males, divided into two groups of 29 patients each: Group 1, patients with cancer of the digestive tract and accessory organs; Group 2 patients with other types of cancers, all admitted to a public hospital. The plasma levels (lipoproteins and total cholesterol, HDL, and triglycerides, for example) w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 24 publications
2
6
0
2
Order By: Relevance
“…Since oxidative stress is considered to be one of the causes of CAD, 12 we have paid attention to some internal indicators related to oxidative stress such as albumin, uric acid, bilirubin, triglycerides, and cholesterol. [13][14][15] In our study, we found that serum level of albumin was decreased while uric acid was increased in CAD patients comparing to that in HCs. Serum albumin is a major antioxidant in extracellular fluids, and reduction in its levels has also been demonstrated to be associated with pemphigus vulgaris, asthma, and allergic rhinitis.…”
Section: Discussionsupporting
confidence: 45%
See 1 more Smart Citation
“…Since oxidative stress is considered to be one of the causes of CAD, 12 we have paid attention to some internal indicators related to oxidative stress such as albumin, uric acid, bilirubin, triglycerides, and cholesterol. [13][14][15] In our study, we found that serum level of albumin was decreased while uric acid was increased in CAD patients comparing to that in HCs. Serum albumin is a major antioxidant in extracellular fluids, and reduction in its levels has also been demonstrated to be associated with pemphigus vulgaris, asthma, and allergic rhinitis.…”
Section: Discussionsupporting
confidence: 45%
“…ROS can destroy cellular lipids, proteins, and DNA by directly attacking them and cause cell and tissue damage. Since oxidative stress is considered to be one of the causes of CAD, 12 we have paid attention to some internal indicators related to oxidative stress such as albumin, uric acid, bilirubin, triglycerides, and cholesterol 13‐15 . In our study, we found that serum level of albumin was decreased while uric acid was increased in CAD patients comparing to that in HCs.…”
Section: Discussionmentioning
confidence: 64%
“…The reasons for the occurrence of sensory changes in cancer patients during periods of CRT (Kwekkeboom, ; Minniti et al, ; Stone and DeAngelis, ) were as follows: sensory changes are primarily caused by neurotoxicity; various processes can also occur as a result of neurotoxicity, which can affect sensory perception. During cancer treatment, tumor cells are destroyed or their growth is suppressed, but normal cells can be affected unintentionally (Maia et al, ). Many studies reported that the ROS levels in patients who received CRT is increased, and imbalance in ROS levels during CRT are known to cause neurotoxicity (Gupta et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…The cellular macromolecules including DNA, protein, and lipids easily interact with ROS; the end products of lipid peroxidation can be used to detect excessive amounts of ROS in the human body (Barrera, ). Therefore, lipoprotein levels have been used as indicators of ROS production in the human body, and its ratio is more useful in predicting the ROS status compared with other individual indicators (Maia et al, ). Changes in sensory perception and lipoprotein levels can be inferred from the same mechanism during periods of CRT based on previous studies.…”
Section: Introductionmentioning
confidence: 99%
“…CK was analyzed by the enzymatic method with commercial kits (Bioclin, Brazil). Lipid peroxidation (damage to lipids) was determined by thiobarbituric acid reactive substances (TBARS) and the results were calculated according to the standard curve made with MDA at 4Μm as previously described (Maia et al, 2014;De Moraes et al, 2017). For CP determination, 100μL aliquots of plasma were mixed in 600 μL of 10mM DNPH or 2M HCl (sample blank) and the tubes were kept at room temperature in the dark for 60 min.…”
Section: R a F Tmentioning
confidence: 99%